Per una cittadinanza globale. Percorsi di vita e traiettorie formative dei giovani - Paolo Diana (Culture e Studi del Sociale, 2018)
Global citizenship is driven by the belief that it is necessary to promote a global conscience, skills, values and attitudes in favor of a more sustainable and inclusive world, able to coun- ter serious criticalities, such as poverty, imbalances, forced migration, climate change, con- flicts, which often accompany current development models. This article is dedicated to the articles that make up this issue of the magazine and which were selected from those pre- sented in the call for paper “Towards Global Citizenship:Life And Training Paths For Youth Peopleˮ. Preliminarily to the description of the selected contributions, it seemed op- portune to dedicate some reflections to a complex theme that can be analyzed through nu- merous approaches and empirical researches.